Hypoceruloplasminemia: an unusual biochemical finding in a girl with Hashimoto's thyroiditis and severe hypothyroidism - Mariella Valenzise; Federica Porcaro; Giuseppina Zirilli; Filippo De Luca; Maurizio Cinquegrani; Tommaso Aversa (PAGEPress Publications, 2018)
Clinical picture of Hashimoto's thyroiditis (HT) may significantly vary in pediatric age, ranging from euthyroidism to subclinical hypothyroidism or hyperthyroidism; only rarely HT presentation may be characterized by a severe hypothyroidism also in pediatric age. Here we describe a 3-year-old Caucasian girl who was admitted to our Clinic due to pericardial effusion, muscle weakness and weight gain. At clinical examination, she presented with bradycardia, pale and round face, pseudohypertrophy of calf muscles and no pitting edema of the limbs. Routine blood investigations showed high serum aspartate and alanine aminotransferase levels, low serum ceruloplasmin without clinical signs of Wilson's disease, dyslipidemia. Thyroid function tests revealed a picture of severe hypothyroidism associated with HT. After the replacement treatment with L-T4, thyroid-stimulating hormone serum levels gradually decreased, with concomitant resolution of pericardial effusion and normalization of ceruloplasmin levels.